Capacity of ZAECA in Conducting Research and Guidance to Fight Corruption in Zanzibar (International Journal of Scientific Research and Management (IJSRM), 2021)
The main focus of this study is to examine the capacity of ZAECA in conducting research and guidance to fight corruption in Zanzibar. The study employed a descriptive case study research design. The target population of this study was employees in the Ministry of Public Services and Good Governance and its Commissions and Authorities including; ZAECA, Commission for Good Governance, Commission of Ethics in Public Services, Commission for Human Rights, Institute of Public Administration, Control Auditor General (CAG) and the office of Director of Public Prosecution (DPP). Judgmental sampling and simple random sampling techniques were used to select a sample size of 85 respondents. The study found that ZAECA does not have sufficient powers to effectively carry out its mandate and the respondents rated a moderate capacity in conducting research and guidance to fight corruption, human resources and independence. The study concludes that ZAECA does not have sufficient powers to effectively carry out its mandate and that ZAECA is not free from undue influence. Finally, the study recommended that the government should ensure that ZAECA is independent and autonomous by clearly delinking it from political influence.